Health professionals and the meaning they apply to women‟s remaining in violent conjugal relationships - Nadirlene Pereira Gomes; Alacoque Lorenzini Erdmann; Jordana Brock Carneiro; Gilvânia Patrícia do Nascimento Paixão; Jamille Araujo de Sousa Santos; Luiz Antonio Bettinelli (Universidade Federal do Ceará, 2013)
The authors aim to investigate the meanings attributed by health professionals working in the Family Health Strategy to women‟s remaining in violent conjugal relationships. The research is based in the method of Grounded Theory. Interviews were held between May and August 2012 with 52 professionals who work in Family Health in a city in the Brazilian state of Santa Catarina. It is indicated that violence is related to the threats made, to the partner‟s involvement in drug trafficking, to economic and emotional dependence, to the valuing of marriage, to the belief in female submission, and to shame. The professionals indicate the need for strategies in defense of a life free from violence for women: psycho-social support; educational activities regarding the social construction of gender; and articulation of policies based on intersectoriality.